Evaluating Türkiye’s Influence in the Somali Peace Process: Positive or Negative Peace? - Huriye Yıldırım Çinar; Asena Boztaş; N. Ceren Türkmen (Güvenlik Stratejileri Dergisi)
This study seeks to examine the role of Türkiye in the peace process in Somalia through the lens of the Peace Studies paradigm. It aims to assess Türkiye’s contributions in light of positive and negative peace concepts developed by Johan Galtung and to determine the extent to which these activities support the establishment of sustainable peace in Somalia. Through a qualitative approach and historical descriptive analysis, the article systematically investigates the theoretical framework of Peace Studies, the historical context, and the current socio-political dynamics of Somalia, as well as Türkiye’s initiatives in Somalia post-2011. The findings suggest that Türkiye’s multi-faceted engagement in Somalia (humanitarian aid, development cooperation, and security sector reform) generally aligns with the positive peace paradigm. Türkiye’s initiatives in Somalia, such as infrastructure development, education and health services improvement, and institutional capacity building, are considered efforts to reduce structural violence. Nevertheless, the analysis emphasizes the need for more comprehensive, long-term, and multi-actor strategies to effectively tackle Somalia’s intricate and multi-layered challenges.